Seasonal Changes of Thyroid Function Parameters in Women of Reproductive Age Between 2012 and 2018: A Retrospective, Observational, Single-Center Study - Fu, Jinrong; Zhang, Guofeng; Xu, Pei; Guo, Rui; Li, Jiarong; Guan, Haixia; Li, Yushu (Frontiers in Endocrinology, 2021)
Background Thyroid function can be influenced by external stimuli such as light and temperature. However, it is currently unknown whether there is seasonal variation of thyroid function in women of reproductive age. Adequate thyroid function in reproductive-aged women is necessary for optimal feto-maternal outcomes. Therefore, this study aims to evaluate the seasonal changes in levels of thyrotropin (TSH), free triiodothyronine (FT3), free thyroxine (FT4) and TSH index (TSHI) in women of reproductive age. Methods A large, retrospective study was conducted that included women aged 20-49 years who visited our outpatient or check-up center between 2012 and 2018. Thyroid function was measured using the automated immunochemiluminescent assay kit. Subjects with overt thyroid dysfunction, pregnancy, thyroid disease, cancer, severe infectious or psychological disease were excluded. Seasonal differences of thyroid function were analyzed using the Kruskal–Wallis test or the analysis of means with transformed ranks. Spearman’s correlation was performed to evaluate the association between thyroid function parameters and age. A subset of 181 subjects were included in the longitudinal analyses, differences in thyroid function between summer and winter were analyzed using the Wilcoxon test. Results A total of 48,990 women with a median age of 39 years were included. The prevalence of subclinical hypothyroidism was lower in summer but higher in winter (5.6% vs 7.0%, P<0.05). The TSH, FT3, FT4 levels and TSHI reached a peak in winter while declined to trough in summer. The TSH concentrations (r=0.044, P<0.001) and TSHI (r=0.025, P<0.001) were positively correlated with age, whereas FT3 (r=-0.073, P<0.001) and FT4 (r=-0.059, P<0.001) were negatively correlated with age. The associations of thyroid parameters with age were similar between subjects with positive thyroid peroxidase antibody (TPOAb) and those with negative TPOAb. In the matched longitudinal analysis of 181 subjects, no significant differences were detected in the thyroid parameters between summer and winter. Conclusions This retrospective single-center study showed that thyroid hormone levels and central sensitivity to thyroid hormones are influenced by age and seasonal fluctuations among women of reproductive age, while its impact on reproductive health remains to be elucidated in future studies.